2023
DOI: 10.3389/fmicb.2023.1169699
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever virus pA104R protein acts as a suppressor of type I interferon signaling

Abstract: This study evaluates the role of the late viral protein, pA104R, in African swine fever virus immunosuppression. ASFV-encoded pA104R is a putative histone-like protein that is highly conserved throughout different virulent and non-virulent isolates. Previous studies have demonstrated that pA104R plays a vital role in the ASFV replication cycle and is a potential target for antiviral therapy. Here, we demonstrated that pA104R is a potent antagonist of type I interferon signaling. IFN-stimulated response element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…In our previous investigation, we identified that pA104R possesses the ability to counteract the host’s innate immune response ( 40 ), thereby impacting its effectiveness as an immunological vaccine. Characterizing the immunodominant epitope of pA104R offers a means to overcome its inhibitory functional sites, enabling the full exploitation of its immunoprotective potential.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous investigation, we identified that pA104R possesses the ability to counteract the host’s innate immune response ( 40 ), thereby impacting its effectiveness as an immunological vaccine. Characterizing the immunodominant epitope of pA104R offers a means to overcome its inhibitory functional sites, enabling the full exploitation of its immunoprotective potential.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Deletion B125R [160], C84L [161], L11L/L7L [162], DP71L [163], DP96R [163], B119L [164], and DP148R [163] significantly reduced the virulence of the virus and showed partial or complete protection against infection with ASFV strains. Besides, a lot of conserved B cell linear epitope in pB602L [165], p34 [166], p30 [167], pA104R [168], and p72 [169] have been identified. About the ASFV vaccine: (1) we can screen the optimal deletion combination of virulence genes (B125R, C84L, L11L/L7L, DP71L, DP96R, B119L, and DP148R) to obtain attenuated and attenuated vaccines; (2) we can concatenate mRNA vaccines that express different immunogenic proteins (p34, p72, p54, p30, and CD2v); and (3) we can also tandem mRNA vaccines that express different B cell linear epitopes (pB602L, p34, p30, pA104R, and p72) of the same immunogenic protein.…”
Section: Discussionmentioning
confidence: 99%
“…MGF360–9 L interacts with and degrades STAT1 and STAT2 via the apoptosis and proteasome pathways ( Zhang et al., 2022b ). pS273R and pA104R lead to the degradation of STAT2 and attenuation of STAT1 phosphorylation, respectively ( Chen et al., 2023 ; Li et al., 2023 ). pI215L triggers the degradation of IRF9 and STAT2 through autophagy-lysosome and proteasome pathways, respectively ( Li et al., 2022 ; Riera et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%